2017
DOI: 10.1037/law0000101
|View full text |Cite
|
Sign up to set email alerts
|

An international human rights perspective on maternal criminal justice involvement in the United States.

Abstract: Internationally and historically unprecedented numbers of women in the United States are under criminal justice supervision in jails, prisons, and the community. Pregnant women and mothers with minor children comprise a large proportion of this population. The rise in criminal justice oversight and incarceration rates has differentially impacted a highly vulnerable population of women and children. This article outlines an international human rights perspective on the criminal justice involvement of pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 86 publications
2
23
0
2
Order By: Relevance
“…Often, infant placement could not be arranged before birth, adding to the mothers ' anxiety. (p. 53) While possibly outdated, these observations are generally consistent with our work with imprisoned women in Minnesota (Shlafer, Gerrity, & Duwe, 2015) and our understanding of the processes and policies in other states (for a review, see Goshin, Arditti, Dallaire, Shlafer, & Hollihan, 2017). Indeed, Kelsey et al (2017) reported that 17.4% of facilities surveyed require incarcerated women to be handcuffed or shackled during the delivery process.…”
Section: Childbirthsupporting
confidence: 77%
See 1 more Smart Citation
“…Often, infant placement could not be arranged before birth, adding to the mothers ' anxiety. (p. 53) While possibly outdated, these observations are generally consistent with our work with imprisoned women in Minnesota (Shlafer, Gerrity, & Duwe, 2015) and our understanding of the processes and policies in other states (for a review, see Goshin, Arditti, Dallaire, Shlafer, & Hollihan, 2017). Indeed, Kelsey et al (2017) reported that 17.4% of facilities surveyed require incarcerated women to be handcuffed or shackled during the delivery process.…”
Section: Childbirthsupporting
confidence: 77%
“…While possibly outdated, these observations are generally consistent with our work with imprisoned women in Minnesota (Shlafer, Gerrity, & Duwe, ) and our understanding of the processes and policies in other states (for a review, see Goshin, Arditti, Dallaire, Shlafer, & Hollihan, ). Indeed, Kelsey et al.…”
Section: Introductionsupporting
confidence: 80%
“…Although some of these women are released before giving birth, each year an estimated 1400 women in the US give birth while incarcerated . As the female prison population has risen, there has been a growing call for gender-responsive policies and programs in carceral settings, including the development and implementation of programs that meet the unique needs of pregnant women in prison (Covington and Bloom 2007;Goshin et al 2017;Sufrin 2017).…”
Section: Introductionmentioning
confidence: 99%
“…O sistema penitenciário brasileiro vem apresentando um formato ineficaz de ressocialização e esse processo ocasiona problemas em escala exponencial de crescimentos. Compreende-se que o crime é um fenômeno complexo que abrange fatores biológicos, ambientais, sociais, econômicos, psicológicos, psiquiátricos, entre outros (Goshin, Arditti, Dallaire, Shlafer, & Hollihan, 2016;Johnston, 2019).…”
Section: Introductionunclassified